2000
DOI: 10.1094/pdis.2000.84.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Management of Dollar Spot on Creeping Bentgrass with Metabolites of Pseudomonas aureofaciens (TX-1)

Abstract: Antifungal extracts from four strains of bacteria that were selected for their ability to inhibit fungal turfgrass pathogens were compared for in vitro activity. The cell extract from Pseudomonas aureofaciens Tx-1 (ATCC 55670) exhibited the greatest antifungal activity against selected turfgrass pathogens. Purification of the extract yielded a single active component that was identified as phenazine-1 carboxylic acid (PCA). Minimum inhibitory concentrations of PCA to tested fungal pathogens ranged from 10 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…Other research has reported the enhanced benefits of applying organic fertilizer in conjunction with conventional fungicides for reducing DSSv (18). This biofungicide study supports the results of published successes of biological control methods for DS on cool‐season turfgrasses (7,13,16,20,21). However, this is the first report of biofungicides successfully controlling DS on warm‐season turfgrass.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Other research has reported the enhanced benefits of applying organic fertilizer in conjunction with conventional fungicides for reducing DSSv (18). This biofungicide study supports the results of published successes of biological control methods for DS on cool‐season turfgrasses (7,13,16,20,21). However, this is the first report of biofungicides successfully controlling DS on warm‐season turfgrass.…”
Section: Resultssupporting
confidence: 86%
“…Extensive research has been conducted on the use of alternative disease management tools to control DS (7,13,16,19,20,21). Biological agents and use of organic fertilizers have been proven to be effective for suppressing dollar spot in cool‐season grasses (16,19,21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some antibiotics, viz. PCA, are being studied to control foliar phytopathogens [25], and hence, fermentative mass production is also being optimized [26].…”
Section: Detection Of Additional Metabolitesmentioning
confidence: 99%
“…Numerous reports indicate that phenazine antibiotic production by strains of Ps. chlororaphis, including Tx-1, and of other Pseudomonas spp., is important for effective control of various rootinfecting pathogens (Bull et al ., 1991;Mazzola et al ., 1992;Carruthers et al , 1995;Pierson III & Pierson, 1996;Chin-A-Woeng et al ., 2000;Powell et al ., 2000;Timms-Wilson et al ., 2000), and this may have been the case with Tx-1 against P. aphanidermatum . Phenazineproducing strains of pseudomonads were effective in controlling several diseases caused by Pythium spp.…”
Section: Shoots Rootsmentioning
confidence: 99%